phân tích đa thức thành nhân tử
x^4y^4+16+(xy+2)^4
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bài 2:
Sửa đề: \(x^3-3x^2-10x=0\)
\(\Leftrightarrow x\left(x^2-3x-10\right)=0\)
\(\Leftrightarrow x\left(x-5\right)\left(x+2\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=0\\x=5\\x=-2\end{matrix}\right.\)
\(x^4-81=\left(x^2-9\right)\left(x^2+9\right)=\left(x-3\right)\left(x+3\right)\left(x^2+9\right)\)
\(=\left(x^2-9\right)\left(x^2+9\right)=\left(x-3\right)\left(x+3\right)\left(x^2+9\right)\)
\(x^4+2x^3+10x-25\)
\(=x^4+5x^2+2x^3+10x-5x^2-25\)
\(=\left(x^2+5\right)\left(x^2+2x-5\right)\)
\(x^4y-3x^3y^2+3x^2y^3+xy^4=xy\left(x^3-3x^2y+3xy^2+y^3\right)\)
Câu 1:
\(=x^2-\left(y-4\right)^2\)
\(=\left(x-y+4\right)\cdot\left(x+y-4\right)\)
\(x^4y^4+16+\left(xy+2\right)^4=t^4+16+\left(t+2\right)^4\)(\(t=xy\))
\(=t^4+16+\left(t^2+4t+4\right)^2=t^4+16+\left(t^2+2t+4\right)^2+4t\left(t^2+2t+4\right)+4t^2\)
\(=\left(t^2+2t+4\right)^2+t^4+4t^3+12t^2+16t+16\)
\(=2\left(t^2+2t+4\right)^2\)
\(=2\left(x^2y^2+2xy+4\right)^2\)